The Results of Public Accommodation Establishments in Northern Hungarian Region, with Special Regard to Heves County - Szabó, Róbert (Acta Agraria Debreceniensis, 2012)
The study shows the results of public accommodation establishments (especially in Heves County) in the period of 2000-2009 in the context of basic touristic statistical indicators like the number of public accommodation establishments, capacity, arrivals, bednights, average length of stay, revenue (structure of revenue). According the study, we can conclude that on the basis of the capacity, number of guests and number of bednights of public accommodation establisments, Heves County (as compared to other counties of the region) played a pivotal role in the tourism of Northern Hungary in the studied period.